Cell transfer technology for tissue engineering - Keiko Akazawa; Kengo Iwasaki; Mizuki Nagata; Naoki Yokoyama; Hirohito Ayame; Kazumasa Yamaki; Yuichi Tanaka; Izumi Honda; Chikako Morioka; Tsuyoshi Kimura; Motohiro Komaki; Akio Kishida; et al. (BMC, 2017)
Abstract We recently developed novel cell transplantation method "cell transfer technology" utilizing photolithography. Using this method, we can transfer ex vivo expanded cells onto scaffold material in desired patterns, like printing of pictures and letters on a paper. We have investigated the possibility of this novel method for cell-based therapy using several disease models. We first transferred endothelial cells in capillary-like patterns on amnion. The transplantation of the endothelial cell-transferred amnion enhanced the reperfusion in mouse ischemic limb model. The fusion of transplanted capillary with host vessel networks was also observed. The osteoblast- and periodontal ligament stem cell-transferred amnion were next transplanted in bone and periodontal defects models. After healing period, both transplantations improved the regeneration of bone and periodontal tissues, respectively. This method was further applicable to transfer of multiple cell types and the transplantation of osteoblasts and periodontal ligament stem cell-transferred amnion resulted in the improved bone regeneration compared with single cell type transplantation. These data suggested the therapeutic potential of the technology in cell-based therapies for reperfusion of ischemic limb and regeneration of bone and periodontal tissues. Cell transfer technology is applicable to wide range of regenerative medicine in the future.